A Universe of Sound: processing NASA data into sonifications to explore participant response - Arcand, Kimberly Kowal; Schonhut-Stasik, Jessica Sarah; Kane, Sarah G.; Sturdevant, Gwynn; Russo, Matt; Watzke, Megan; Hsu, Brian; Smith, Lisa F. (Frontiers in Communication, 2024)
Historically, astronomy has prioritized visuals to present information, with scientists and communicators overlooking the critical need to communicate astrophysics with blind or low-vision audiences and provide novel channels for sighted audiences to process scientific information. This study sonified NASA data of three astronomical objects presented as aural visualizations, then surveyed blind or low-vision and sighted individuals to elicit feedback on the experience of these pieces as it relates to enjoyment, education, and trust of the scientific data. Data analyses from 3,184 sighted or blind or low-vision survey participants yielded significant self-reported learning gains and positive experiential responses. Results showed that astrophysical data engaging multiple senses could establish additional avenues of trust, increase access, and promote awareness of accessibility in sighted and blind or low-vision communities.